Emotional Disorders, Dispositional Mindfulness, and Mediating Role of Acceptance in Undergraduate and Postgraduate Students - Vibhuti Gupta; Nishit Kumar Sinha (Vikalpa, 2023)
‘For after all, the best thing one can do when it is raining is, let it rain.’ ( Longfellow, 1906 ) Mental health conditions, including depression, anxiety, and stress, affect a sizable proportion of university students. Yet, little is known regarding the incidence of mental health issues among Indian university students. These mental health issues are generally caused by a range of factors, including academic demands, interpersonal connections ( Steptoe, 2007 ), future prospects, competitive exams, peer pressure, and professional considerations ( Beiter et al., 2015 ). One of the most important mental health problems impacting a large population across India and the world is depression, leading to physical diseases, suicidal thoughts, and suicide, among other negative outcomes ( Gururaj et al., 2016 ). According to the NCRB Report, 2021, the two age groups most susceptible to suicide were between 18 and 30 and 30 and 44. Suicide rates in both age categories were 34.5% and 31.7%, respectively. Family issues (3,233 victims), romantic relationships (1,495 victims), and illness (1,408 victims) were the three leading factors in suicides below 18 years of age, while the victims that were either students or unemployed made up 8.0% (13,089 victims) and 8.4% (13,714 victims) of all suicides, respectively. The objectives of this study were to understand and add to the body of knowledge on the role of mindfulness concerning depression, anxiety, and stress amongst university students; the role of mindfulness concerning avoidant behaviours amongst university students; and the mediating role of acceptance in the relationship between mindfulness and depression, anxiety, and stress amongst university students. The results of the study revealed that depression, experiential avoidance, and mindfulness are all strongly and negatively connected. The study discovered a strong correlation between experiential avoidance and depression, anxiety, and stress (psychological distress). Mindfulness had a considerable impact on the mediator, experiential avoidance, which was postulated.